Elderly perform lower number of repetitions maximum than young at low instead high load resistance exercise - Sardeli, Amanda Veiga; Santos, Lucas do Carmo; Ferreira, Marina Lívia Venturini; Gásparia, Arthur Fernandes; Santos, Wellington Martins dos; Cavaglieri, Cláudia Regina; Chacon-Mikahil, Mara Patrícia Traina (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Aging process is characterized by reduction of muscle mass and strength, named sarcopenia. To attenuate these declines, resistance training has been purposed. The use 1RM test has been applied to define the maximal strength and prescription of exercise. Otherwise, it is not safe and it has not shown good practical applicability. Thus, the present study aim to compare the repetitions number for high and low load resistance exercise performed until failure between a young and elderly men groups. Methods: We compared (Mann-Whitney test) the repetitions number performed until muscle failure by 9 young and 9 elderly men at four sets 45ºleg press exercise for high (80% 1RM) and low load (30% 1RM). Results: Both groups reached maximum values for rate of perceived exertion, ensuring the muscle failure were achieved and no differences were seen between groups. The repetitions numbers were higher for young men with similar delta of reduction throughout sets between groups at low load resistance exercise. Otherwise, the delta of repetitions number reduction throughout sets at high load resistance exercise was higher for young men than elderly. Conclusions: We conclude elderly people need to perform lower number of repetition to reach muscle failure and thus achieve the desired training stimulus, mainly in low load resistance exercise. Furthermore, as they have better resistance to fatigue along sets the reduction of repetition number along sets is lower for them mainly when high load resistance exercise is performed.